EVALUASI KINERJA RUTE KENDARAAN ANGKUTAN BARANG KOTA DUMAI DAN PEMODELAN MENGGUNAKAN APLIKASI PTV VISUM 22 - SITI WAH YUNI (Jurnal TeKLA, 2022)
Dumai City is a developing area, especially in the industrial sector. This is evidenced by the large number of large industries in Dumai City. The existence of this industry means that there are goods transportation that operates and of course it also affects the condition of the road pavement. Currently, the arrangement is managed by the Dumai City Transportation Service. The current route (the Existing Route) is the Provincial and National Road Routes. It is known that this route is a priority road where this road is the only road that connects the vehicle to a destination such as a factory or PT in Dumai City. So that in this condition causes an increase in the volume of the route traversed. From the problems that occur, it is necessary to evaluate the performance of the freight vehicle route to find out whether the route is still feasible to accommodate the vehicles being passed. The method that can be used to analyze the performance of the freight transport route is the Indonesian net capacity guideline (PKJI) 2014. With the development of technology, it can make it easier to provide a visual description or simulation of the condition of the route being evaluated, the software used as a tool in modeling namely PTV Visum 22. From the performance evaluation of the route of the freight vehicle using the 2014 PKJI method, the route of the freight vehicle is still able to accommodate the volume of passing vehicles. However, on Jalan Soekarno Hatta (Rawa Panjang) there is almost a traffic jam where the service level is D, which is approaching an unstable flow where almost all drivers will be restricted (disturbed). The volume of service is related to the capacity that can be tolerated, and it is recommended to do road widening and the results of modeling using the PTV Visum 22 application show that the highest loading of freight vehicles occurs on Jl. Soekarno Hatta (Rawa Panjang) which connects zone 1 to zone 2 is 246 movements.